New Coleoptera records from New Brunswick, Canada: Trogossitidae, Cleridae, and Melyridae, with an addition to the fauna of Nova Scotia - Reginald Webster; Jon Sweeney; Ian DeMerchant (ZooKeys, 2012)
Grynocharis quadrilineata (Melsheimer) and Tenebroides corticalis (Melsheimer) of the family Trogossitidae are newly recorded for New Brunswick, Canada. Additional records of the recently reported Calitys scabra (Thunberg) and Ostoma fraterna (Randall) are presented for the province. The record of O. fraterna is the first recent record of this species from New Brunswick. Additional New Brunswick records of the thaneroclerine, Zenodosus sanguineus (Say), are given, indicting that this species is common and widespread in the province. One species of Cleridae, Cymatodera bicolor (Say), is newly reported from New Brunswick, and the adventive Thanasimus formicarius Linnaeus is newly recorded from Nova Scotia and the Maritime provinces. Attalus morulus (LeConte) and Dolichosoma foveicolle (Kirby), family Melyridae, are reported for the first time for New Brunswick and the Maritime provinces. Collection, habitat data, and distribution maps are presented for these species.